KERJASAMA EKSPOR KOPI MANDAILING KE KOREA SELATAN TAHUN 2016 - Tri Edo Syaputra; Tri Joko Waluyo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research explains about the export cooperation of mandailing coffee to South Korea in 2016. The demand, consumption and many coffee shop in South Korea become a change for Indonesian’s coffee to be exported to that country for filling the coffee need. South Korea imports coffee from various countries of main coffee producers in the world such as Brazil, Colombia, Vietnam and Indonesia. The consumption trend of coffee drinking in South Korea that makes coffee is admired especially mandailing coffee that is exported to South Korea.The method that is used in this research is qualitative research. The datas come from book, journal, thesis, article, website and other sources that are involved with the research. This research focus is how the export process of mandailing coffee to South Korea happens. This research uses liberalism perspective and international cooperation theory.The export cooperation of Mandailing Arabica coffee to South Korea uses the facilitation of third country. The export cooperation of Mandheling Arabica coffee produces cooperation partnership in period of 3 years f2016-2019. The export cooperation partnership in 2016 with import value USD 1 Million. The export of Mandheling Arabica coffee is in the shape of green bean.Keywords: Mandailing Coffee, Exports, International Cooperation